Evaluation of treatment of effluents contaminated with rifampicin by Fenton, electrochemical and associated processes. (April 2018) - Duarte, José Leandro da Silva; Solano, Aline Maria Sales; Arguelho, Maria L.P.M.; Tonholo, Josealdo; Martínez-Huitle, Carlos A.; Zanta, Carmen Lúcia de Paiva e Silva
Abstract: Concerns about the preservation of aquatic ecosystems are growing, drugs that are recalcitrant to conventional treatments can be accumulated in public water supplies and contaminate groundwater. Many technologies, including the Fenton reaction and electrooxidation processes, have been evaluated to remove drugs from water, in the last years. However, the association of different approaches can be a suitable solution when only one technology is not enough. In this frame, this study compares the use of the Fenton reaction, the electrochemical process and coupled process to treat a synthetic effluent containing a potential pollutant, rifampicin. Regarding the electrode materials studied herein, efficiency of rifampicin degradation decreased in the following order: Boron-doped diamond (BDD) >> Ti/Pt > Ti/Ru0.3 Ti0.7 O2 (DSA, Dimensionally stable anode). The better performance of BDD was associated to the species BDD(OH), which degrades organic compounds more efficiently than the species RuO(x+1) and PtO(x+1) . The electrochemical reaction employing BDD was as efficient as the Fenton reaction where 80% of chemical oxygen demand (COD) was removed. However, the Fenton reaction was faster. Results also clearly showed that, when both technologies were associated, no significant improvements were achieved. Nevertheless, when hydrogen peroxide was added to the electrochemical process, a remarkable enhancement of the reaction efficiency was attained, especially in the case of BDD, requiring less energy for treatment this kind of effluent.